A Gendered-based Study of Discourse Markers in “Shaw’s Arms and the Man” - Abbas Ibrahim Azeez; Ayad Hameed Mahmoud; Ahmed Adel Nouri (Universitas Muhammadiyah Barru, 2023)
This study is intended to investigate the difference between males and females in terms of using discourse markers. The study hypothesizes that gender influences the frequency and type of discourse markers employed by participants, and that males use more discourse markers than females. It is also hypothesized that the differences between females and males in terms of using discourse markers are not only gendered-based, but can also be attributed to some situational and social factors. The present study follows two types of procedures: theoretical and practical. The theoretical part consists of presenting a theoretical framework of discourse markers, while the practical part consists of selecting samples from “Shaw’s Arms and the Man”, and analyzing them in the light of an eclectic model. The adopted model consists of two levels: situational, and pragmatic. The results of analyzing the selected dramatic texts show that males use more discourse markers than females. Both males and females employ discourse markers for different purposes due to the gendered features socially ascribed to them. The results also show that social relationship, social distance, social status, the mood of the speaker, the topic they talk about, type of text, its setting, and its theme, have a vital impact on the frequency and type of socially employed by males and females.